Influence of the gutta-percha taper and finger spreader on lateral condensation effectiveness - Adinael Trindade-Junior; Juliane Maria Guerreiro-Tanomaru; Raqueli Viapiana; José Mauricio Santos Nunes Reis; Mario Tanomaru-Filho (Revista Sul-Brasileira de Odontologia, 2015)
Lateral condensation effectiveness may be influenced by the gutta-percha and finger spreader taper used during root canal obturation. Objective: To evaluate the penetration ability of finger spreader into simulated root canals prepared using MTwo rotary system and filled with different gutta-percha and finger spreader tapers. Material and methods: Resin blocks with curved root canals had the apical diameter enlarged up to #25.06 and distributed into groups (n = 6) according to the gutta-percha taper (#25.02, #25.04, and #25.06) and the finger spreader (#30 and #35 NiTi, and stainless steel B) used to perform cold lateral condensation. After applying a load of 1.5 Kg over the finger spreaders’ head, the distance between the finger spread tip and the apical limit of the root canal preparation were obtained. The data were submitted to Anova and Tukey-Krammer’s test, with 5% of significance. Results: The gutta-percha cones with 0.02 taper enabled higher finger spreader penetration when compared to 0.04 and 0.06 tapers (p < 0.05), which were similar between each other (p > 0.05), regardless of the type and diameter of the finger spreader used. When different finger spreaders were compared among themselves, stainless steel B showed higher penetration ability (p < 0.05). Conclusion: It was concluded that the stainless-steel finger spreaders showed superior penetration ability and gutta-percha with lower tapers enabled a more effective lateral condensation at the apical third.